A Study on Trans-para-Sasakian Manifolds - Erken, Irem Küpelı; Özkan, Mustafa (My University, 2024)
In the current paper, we make the first contribution to investigate conditions under which three-dimensional trans-para-Sasakian manifold has ?-parallel Ricci tensor and cyclic parallel Ricci tensor. Finally, a three dimensional trans-para-Sasakian manifold example which satisfies our results is constructed
Keywords: Trans-para-Sasakian manifold; ?-parallel Ricci tensor; Cyclic Ricci tensor.